Study of Vegetation's Capacity to Reduce of the CO2 Emissions from Vehicle Engine Contribution in Green Open Space Pinang Masak Campus, Jambi University Reevaluation on Period 2016–2022 - Tazkiah Auliaputri; Ulan Aprilia; Fitra Nurhanipan; Robet Suhanda; Jumiatun Nazila; Mahya Ihsan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The atmosphere's carbon dioxide (CO2) content raises global temperatures. OGS, or green open space, has the power to absorb carbon dioxide. The OGS of Pinang Masak Campus, Jambi University, too has this potential, although the number of vehicles keeps rising yearly. The reduction of flora at Jambi University's Pinang Masak Campus will result in higher carbon emissions. The three-month study was carried out at the Pinang Masak Campus Jambi University. This study directly measured the crown and counted the number of individual trees. There are 62 species of trees in all, totaling 1455 individuals. Motorcycles are the most common form of vehicle to enter the college area. According to calculations of carbon absorption, the rates of emissions produced by cars, 583,619 kg/hour, and 581,779.330 kg/hour, respectively, are 1,839.667 kg/hour, 583,619 kg/hour, and 581,779.330 kg/hour, respectively. According to these findings, based on positive residual emissions, the Green Open Space of Pinang Masak Campus is less able to absorb carbon emissions from automobiles.